Relationship between google meet learning media and nursing student GPA STIKES ST Elisabeth Semarang - Maria Theresia Priyastuti (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to explore how nursing students use social media in their learning formally and informally. Social media has become a most inseparable part of young adults' lives with the rapid development of statistics and communique generation.The observe aimed to assess using social media and its affiliation with instructional overall performance, nicely-being, and interpersonal relation of the fitness sciences undergraduates. This study discusses the relationship between Google meet mastering media and the Grade Point Average (GPA) of Stikes St. Nursing students. Elisabeth Semarang at some point of the coronavirus pandemic. Google Meet (GM) media is the media most often used by Stikes St. Lecturers. Elisabeth Semarang in studying. The cause of this take a look at changed into to determine the relationship between Google meet getting to know media and the Grade Point Average (GPA) of nursing students. The method used is quantitative descriptive research with a complete sampling of degree III college students of the S1 Nursing Study Program, Stikes St. Elisabeth Semarang during the online studying technique. This research became carried out by using administering questionnaires related to Google Meet studying media and GPA of nursing college students obtained at some stage in on-line mastering all through the Covid-19 period. The outcomes confirmed that there was a dating between Google Meet getting to know media and the IPK of Nursing Stikes St. Students. Elizabeth Semarang.